ASSASSINS TREMBLING EAST - Abbas Eshmurodov (Journals Park Publishing, 2022)
Assassins (aka Nizari Ismailis) were strong in Persia and Syria from the 13th century AD until their defeat at the hands of the Mongols in the mid-11th century. Shia Muslims were a heretical group. Safe in their towers on a solid hill, they were embarrassed by the strategy of isolating and killing opposition figures, usually in knife-wielding communities. The killers known as the group are hashish by their enemies in relation to their use, ‘killer’ is the corruption of the Arabic language (‘hashish eater’) and therefore the name has become associated with their boss modus operandi, political or religious murder targets . The Nizari Ismailis still exist today as a part of Islam.
Keywords: assassin; hashishun; strategy